Conjoined twins: Parapagus dithoracicus - Juković Fehim (Srpski Arhiv za Celokupno Lekarstvo, 2018)
Introduction. Throughout history, various types of conjoined twins have been described, many of whom lived until adulthood. The anomaly includes several varieties, with parapagus being one of the rarer forms of conjoined twins. The aim of this paper was to present a rare case of conjoined twins – parapagus type. Case outline. In this paper we present autopsy and radiologic findings in male 40-week-old parapagus twins from a monozygotic pregnancy, with multiple anomalies in different systems of organs and musculoskeletal systems. Parapagus twins have a side-to-side connection with shared pelvis and can be defined as one of three subtypes. In our case, it was a dithoracic parapagus subtype, with four upper and three lower limbs (tetrabrachius tripus), where the presence of the third bizarre-looking lower limb made the case even more unusual among the rare type. Both parents were drug addicts with a history of sedative abuse. The mother had regular sonographic examinations during pregnancy. Conclusion. Adequate early prenatal diagnosis of conjoined twins and possible termination of such a pregnancy are the key reasons for rare occurrence of such cases. Failure to recognize a pathological pregnancy and its maintenance until the delivery, despite regular gynecological examinations, is why our case is unique in comparison to contemporary literature.